Extending Shay's double truth: toward a nuanced view of subjectivity and objectivity in assessment practices. Issue 8 (17th November 2022) - Walton, Jack; Wolff, Karin
ABSTRACT: In her early work, Suellen Shay argues that higher education tends to valorise objective notions of reality while downplaying the subjectivity of individuals. In Shay's view, this one-sided approach leads to a deficiency in the preparation of students for the holistic reality of the world they will experience beyond university. Taking Shay's provocation as a starting point, this paper explores a framework for both the design and analysis of educational assessment practices, with the aim of accounting for both objectivity and subjectivity in serving as legitimate bases for educational experiences. We follow Shay in adopting concepts from Legitimation Code Theory to achieve this, and, drawing on our own experiences and prior work, discuss how this framework may be applied.